VARIATION IN THE RESISTANCE OF FABA BEAN (Vicia faba L.) TO ASCOCHYTA BLIGHT - Uyek Malik Yakop (Department of Agronomy Faculty of Agriculture University of Mataram and Indonesian Society of Agronomy Branch NTB, 2009)
ABSTRACT Faba bean (Vicia faba L.) is important grain legumes in the world as it is a source of protein in the human diet, used as animal feed and for crop rotation to break disease cycles of cereals. Faba bean is adversely affected by a fungal disease Ascochyta blight (Ascochyta fabae) which limit productivity and production in some countries. There was variation among putatively resistant accessions in their response to various isolates of A. fabae. The present study was conducted to identify variation in the resistance of several faba bean accessions to isolates of A. fabae and variability of virulence among the isolates. The experiment was conducted in two stages using two different seed samples, namely bulk samples and single plant derived pure lines. Eight accessions tested were Acc299, 303, 342, 508, 680, 948, 970 and Ascot, while eight isolates used included 252/92, A26, 166/92, 493/92, 219/92, 260/92, 331/91 and 526/92. The reaction of pure lines of Acc 303, 680, 948, 970 and 622 or Ascot were resistant to all isolates tested, while Acc 299 and 508 were resistant to several isolates, but not all. The pathogenic variability of isolates of A. fabae was apparent. This is based on the fact that some isolates (331/91 and 526/92) caused more disease on all accessions while other isolates caused disease on either most, or only a few accessions. Isolate 331/91 resulted in the greatest discrimination between resistant and susceptible accessions and for this reason it was suggested to select for genetic studies in the resistance of faba bean (Vicia faba L.) to Ascochyta blight. ABSTRAK Kacang babi (Vicia faba L.) adalah kacang-kacang yang penting di dunia karena merupakan sumber makanan yang mengandung protein, dapat digunakan sebagai makanan ternak dan sebagai tanaman untuk pergiliran tanam serealia dalam usaha memotong siklus keberadaan penyakit. Kacang babi rentan terhadap serangan jamur bercak daun Ascochyta (Ascochyta fabae) yang dapat menurunkan produktivitas dan hasil tanaman di beberapa negara. Terdapat perbedaan respon yang nyata diantara galur-galur yang tahan terhadap isolat A. fabae. Penelitian ini telah dilakukan dengan tujuan untuk mengidentifikasi vasiasi ketahanan beberapa aksesi kacang babi terhadap beberapa isolat A. fabae dan variabilitas virulensi diantara isolat-isolat tersebut. Percobaan dilakukan dua tahap dengan menggunakan sampel benih yang berbeda, yaitu sampel bulk dan tanaman tunggal berasal dari galur murni. Delapan galur yang di uji antara lain Acc299, 303, 342, 508, 680, 948, 970 dan Ascot, sedangkan delapan isolat yang digunakan antara lain adalah 252/92, A26, 166/92, 493/92, 219/92, 260/92, 331/91 and 526/92. Reaksi dari beberapa galur murni (Acc 303, 680, 948, 970 dan 622 atau Ascot) adalah tahan terhadap semua isolat yang diujikan, sementara Acc 299 dan 508 hanya tahan terhadap beberapa isolat saja, dan tidak terhadap semua isolat yang diujikan. Variabilitas virulensi dari isolat-isolat A. fabae tampak nyata mengingat dua isolat (331/91 and 526/92) menyebabkan infeksi terhadap semua genotipe sementara isolat yang lain menimbulkan penyakit hanya terhadap beberapa genotipe saja. Isolat 331/91 menunjukkan diskriminasi yang paling tinggi antara penampakan rentan dan tahan dari aksesi-aksesi, sehingga isolat tersebut dapat disarankan untuk dapat digunakan di dalam pengujian lebih lanjut untuk ketahanan kacang babi (Vicia faba L.) terhadap Ascochyta fabae.